The role of platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio as a supplemental tool for differential diagnosis of uterine myoma and sarcoma - Yoon Young Jeong; Eun Ji Lee; Eun Byeol Cho; Jung Min Ryu; Youn Seok Choi (Clinical and Experimental Obstetrics & Gynecology)
Background: The purpose of this study was to investigate whether the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) can be used as supplemental tools to differentiate between uterine myomas and sarcomas. Methods: From January 2000 to May 2020, patients diagnosed with uterine sarcoma or myoma after surgery at the Catholic University Hospital of Daegu were enrolled in the study. The age and preoperative hematologic findings including hemoglobin, white blood cell count, neutrophils, lymphocytes, platelet counts and lactate dehydrogenase were retrospectively investigated. Results: A total of 366 patients, including 40 uterine sarcoma patients and 326 uterine myoma patients, were included in the study. Among the hematologic findings, NLR and PLR showed statistically significant differences between uterine sarcoma and myoma. The probability of sarcoma was high when NLR was ≥2.6 and PLR was ≥150.0. When NLR was ≥2.6, the odds ratio of uterine sarcoma risk was 9.761 (95% confidence interval [CI]: 3.950–24.120, P < 0.001). When PLR was ≥150, the odds ratio of uterine sarcoma risk was 3.502 (95% CI: 1.528–8.027, P = 0.003). If NLR was above their cut-offs, the sensitivity of uterine sarcoma diagnosis was 60% and specificity was 83.4%. Identically, PLR was 60% and 73.3%, respectively. Conclusion: NLR and PLR are useful supplemental tools for the differential diagnosis of uterine myoma and sarcoma. Therefore, more expensive and accurate imaging studies, such as magnetic resonance imaging, can be more effectively recommended when these hematologic findings are used together with pelvic ultrasonography.